ENTREPRENEURSHIP’S CONDITION AND DIRECTIONS OF DEVELOPMENT IN THE REGION OF THE LOCAL ACTION GROUP ‘FLINT CIRCLE’ - Piotr Gabryjończyk; Magdalena Iwańska (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article presents entrepreneurship’s condition and directions of development in the region of Local Action Group ‘Flint Circle’. It contains region’s inhabitants opinions about their material status, natural values’ attractiveness and condition of the technical infrastructure. The article also presents current and preferable forms of the economic activities, as well as inhabitants’ will for self-commitment to regional development. The case study is based on secondary data, obtained from Local Action Group ‘Flint Circle’.